O autoconhecimento da mens no livro X do De Trinitate de Santo Agostinho - Andrade, Marcelo Pereira de (2007)
This work shows the analysis which Augustine makes in De Trinitate s tenth book about self-knowledge s process of the mens. For Augustine, the knowledge which the mens has of herself is immediate, total and indubitable. Nevertheless, he recognizes the possibility of the self-deceit and explains that it is possible due the inadequacies between self-knowledge and self-thought